Morphology and elemental behaviour in the alteration layer of borosilicate glass in simulated groundwater. Issue 7 (3rd August 2018) - Du, Xin; Yuan, Wei; Peng, Haibo; Chen, Liang; Wang, Tieshan
ABSTRACT: To understand the behaviour of nuclear waste glass in groundwater, borosilicate glasses were placed in simulated groundwater for more than 200 days. The composition of the simulated groundwater was similar to that of the groundwater in Beishan (a potential nuclear waste site). The pH value of groundwater was adjusted to 7.5, and the ratio of the surface area of glass to the volume of the solution ( SA/V ) was set to 10 m −1 . Solutions and bulk glasses were characterised to obtain the elemental behaviour and surface morphology of the glass/solution interface, which was named the alteration layer. The mean thicknesses of the alteration layer were 5.16 ± 0.11 µm and 11.67 ± 0.28 µm at 70°C and 90°C, respectively. A thicker alteration layer was attributed to the lower surface activation energy of the glass and a high ion exchange between K + and Na + in the interface between the glass surface and the solution. For the elemental behaviour, mobile species B and Na were depleted, while K and Ca from the solution were enriched in the alteration layer due to ion exchange. Network species Si decreased in the layer, leading to the corrosion of the backbone of the glass; however, species Al increased, which implied that some [SiO4 ] units were partially replaced by [AlO4 ] units. In this work, glass in groundwater suffered much more intense corrosion than that in de-ionised water.